A phylogenetic perspective on the influence of ecological attributes on selected species of Astragalus. Issue 3 (2nd October 2017) - Dolarslan, Melda; Gül, Ebru; Acar, Emine; Turktas, Mine
ABSTRACT: The use of phylogeny in ecology has gained attention due to its benefits in understanding biological diversity and adaptation processes. In this study, phylogenetic positions of 12 Astragalus taxa were evaluated by comparing with 419 Astragalus taxa sequences in a database. Additionally, the influence of ecological traits on morphology was assessed. Although the samples were grouped according to subgenera or sections they belong to, this division was not striking. The phylogenetic relationships of the nine endemic and three common Astragalus taxa based on nrDNA region sequences and morphological features as well as their interplay with the environment were examined. Furthermore, soil characteristics of the fields where each Astragalus taxon grows were determined. Analysis of the sequences revealed that the 12 taxa were grouped into three clades using the Bayesian Inference method. A cladogram of 431 Astragalus taxa showed that the samples were divided into ten major clades. Morphological traits were found to be correlated with soil properties, which could indicate adaptation to environmental conditions of these taxa.